The hermeneutics rule as a system of meaning and production of text - Catoggio, Leandro Martín (Estudios de Filosofía, 2012)
This work has as its purpose to show how the Hermeneutics Rule as described by Hans-Georg Gadamer in Wahrheit und Methode represents a system of signification that produces text. For it the semiotics of Iuri Lotman will be employed as well as the Connotative Semiotics of Hjelmslev as theoretical partnerships that enable a greater analyticity of the regulation of the Hermeneutics Rule in the phenomenon of understanding.